Determinants of mortgage default and consumer credit use: The effects of foreclosure laws and foreclosure delays - Sewin Chan; Sewin Haughwout; Andrew Hayashi; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2015)
The mortgage default decision is part of a complex household credit management problem. We examine how factors affecting mortgage default spill over to other credit markets. As home equity turns negative, homeowners default on mortgages and HELOCs at higher rates, whereas they prioritize repaying credit cards and auto loans. Larger unused credit card limits intensify the preservation of credit cards over housing debt. Although mortgage non-recourse statutes increase default on all types of housing debt, they reduce credit card defaults. Foreclosure delays increase default rates for both housing and non-housing debts. Our analysis highlights the interconnectedness of debt repayment decisions.
Keywords: D12; D14; G1; K10; 330; mortgage default; state foreclosure law; consumer finance